Modeling water resource systems within the framework of the MIT Integrated Global System Model: IGSM‐WRS. (17th September 2013) - Strzepek, Kenneth; Schlosser, Adam; Gueneau, Arthur; Gao, Xiang; Blanc, Élodie; Fant, Charles; Rasheed, Bilhuda; Jacoby, Henry D.
<x xml:space="preserve">Abstract</x> [1] Through the integration of a water resource system (WRS) component, the MIT Integrated Global System Model (IGSM) framework has been enhanced to study the effects of climate change on managed water‐resource systems. Development of the WRS involves the downscaling of temperature and precipitation from the zonal representation of the IGSM to regional (latitude‐longitude) scale, and the translation of the resulting surface hydrology to runoff at the scale of river basins, referred to as assessment subregions (ASRs). The model of water supply is combined with analysis of water use in agricultural and nonagricultural sectors and with a model of water system management that allocates water among uses and over time and routes water among ASRs. Results of the IGSM‐WRS framework include measures of water adequacy and ways it is influenced by climate change. Here we document the design of WRS and its linkage to other components of the IGSM and present tests of consistency of model simulation with the historical record.